Menumbuhkan Jiwa Kewirausahaan Siswa SMP IT Madani Pekanbaru - Anggraini, Nia; Lussianda, Erfa Okta; Febrina, Liga; Afwa, Awliya; Adrian, Muhammad (ISEI Cabang Pekanbaru, Koordinator Provinsi Riau, 2023)
SMP IT Madani Pekanbaru is one of the private junior high schools in Pekanbaru City. This school is a mentoring partner who has limited knowledge about entrepreneurship in developing students' potential to be able to choose products that are easy to market. The students are children whose parents' economic income levels are on average below the UMR income standard, so it is necessary to grow and motivate students to become entrepreneurs after participating in the learning process. Students need assistance in opening entrepreneurial insights and knowledge and choosing products to be marketed. The platforms used as mentoring materials are lectures, discussions, and service learning. Through this counseling the students have an entrepreneurial spirit so that their enthusiasm is high to become an entrepreneur. The service learning mentoring method can improve students' ability to market a product, they also know and can choose what kind of product to market, get it easily and sell it quickly so that it can help the family's economy.